Analisis Sentimen pada Ulasan Kegiatan Seminar Nasional Sistem Informasi dan Teknologi Komputer 2023 menggunakan Natural Language Processing (NLP) - Turnandes, Yogo; Ade Irwanda, Ahmad; Vebby (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2024)
This research aims to analyze the sentiment of participant reviews of the National Seminar on Information Systems and Computer Technology 2023 using Natural Language Processing (NLP). With the increasing use of social media and online platforms, sentiment analysis is becoming an important tool to manage and summarize information from diverse participant opinions. This research uses an NLP model adapted to the Indonesian language to provide more contextual and in-depth insights. The research process involved review data collection, data pre-processing, tokenization, stopword removal, stemming, and sentiment analysis using the Naive Bayes algorithm. The analysis results showed that 90% of the reviews were positive, with the most appreciated aspects including the quality of the seminar materials and the availability of facilities. Meanwhile, 10% of reviews were negative, mainly related to time management and interaction with speakers. These findings provide concrete guidance for organizers to focus on improving the less satisfactory aspects. Evaluation of the effectiveness of the NLP model showed that the technique was able to identify sentiment with higher accuracy than conventional methods, reinforcing the potential of NLP as an effective tool in local language-based sentiment analysis. This research contributes to the development of sentiment analysis methodology in the context of Indonesian language, as well as providing valuable references for further research in the field of sentiment analysis.